Optimization of renal transfection using a renal suction-mediated transfection method in mice. (27th May 2016) - Taniguchi, Yota; Kawakami, Shigeru; Fuchigami, Yuki; Oyama, Natsuko; Yamashita, Fumiyoshi; Konishi, Satoshi; Shimizu, Kazunori; Hashida, Mitsuru
Abstract: Background : We previously developed a suction-mediated transfection method in mice. Purpose : The purpose of this study was to optimize the suction-mediated transfection conditions using a pressure-controlled computer system for efficient and safe kidney-targeted gene delivery in mice. Methods : Naked pCMV-Luc was injected into the tail vein in mice, and then the right kidney was suctioned by a device of the suction pressure-controlled system. The effects of renal transfection conditions, such as the suction pressure degree, suction pressure waveform and device area were evaluated by measuring luciferase expression. In addition, renal injury was examined. Results : The renal suction-mediated transfection method at −30 kPa showed high transgene expression. The renal suction waveform did not affect the transfection activity. Under the optimized conditions, the high transgene expression was mostly observed at the renal suctioned site. The transfection conditions used did not induce histological defects or increases in two renal injury biomarkers (Kidney injury molecule-1 mRNA and Clusterin mRNA). Discussion and conclusion : We have clarified the transfection conditions for efficient and safe transfection in the kidney using the suction-mediated transfection method in mice.